Genetic Basis of a Violation of Dollo’s Law: Re-Evolution of Rotating Sex Combs in Drosophila bipectinata - Seher, Thaddeus D. (Genetics Society of America, 2012)
Phylogenetic analyses suggest that violations of “Dollo’s law”—that is, re-evolution of lost complex structures—do occur, albeit infrequently. However, the genetic basis of such reversals has not been examined. Here, we address this question using the Drosophila sex comb, a recently evolved, male-specific morphological structure composed of modified bristles. In some species, sex comb development involves only the modification of individual bristles, while other species have more complex “rotated” sex combs that are shaped by coordinated migration of epithelial tissues. Rotated sex combs were lost in the ananassae species subgroup and subsequently re-evolved, ∼12 million years later, in Drosophila bipectinata and its sibling species. We examine the genetic basis of the differences in sex comb morphology between D. bipectinata and D. malerkotliana, a closely related species with a much simpler sex comb representing the ancestral condition. QTL mapping reveals that >50% of this difference is controlled by one chromosomal inversion that covers ∼5% of the genome. Several other, larger inversions do not contribute appreciably to the phenotype. This genetic architecture suggests that rotating sex combs may have re-evolved through changes in relatively few genes. We discuss potential developmental mechanisms that may allow lost complex structures to be regained.